APPEALS COMMISSION OF THE PRESS COUNCIL -a year later- - Ivošević, Zoran (Pravni zapisi, 2013)
The Appeals Commission of the Serbian Press Council was “imported” from Norway, where it exists for over a century. In Serbia, it was established in November 2009, and started to operate in October 2011. The Commission is comprised of representatives of the media industry, of professional journalists' associations and of the general public, that is, of the “civil society”. The Commission operates in accordance with the Rules of Procedure and passes decisions pursuant to the Code of Ethics of Serbian Journalists. The sessions are chaired by the chairperson, who is one of the Commission members, with a six-month term of office, and are prepared by the secretary general. The work of the Commission and its decisions concern the printed media which have agreed to self-control in implementing the standards of journalist's professional ethics. In one year of operation the Commission has solved over thirty cases, sixteen of which are presented in this paper. Key words: Appeals Commision, Press Council, Code of Serbian Journalists, Commission composition and sessions, practice in case resolution.